New type of metal targets - Bukharov, A.V.; Ankudinov, V.B.; Ogorodnikov, V.P.; Marukhin, Y.A. (Вопросы атомной науки и техники, 2014)
Now the technologies based on interaction of high-intensity beams with substance of a target are being intensively developed. As a target it is possible to use the new type of monodisperse metal targets. The principal advantages of new targets type are: target cooling isn't required; there is no induced activity: the target can be used many times; small dispersion on the speed, the size and interaction points with a beam. The basis of a target is the jet of molten metal, following in the vacuum chamber .Under the influence of the special disturbance superimposed on the liquid jet, the jet disintegrated into identical drops. In the vacuum chamber the drops freeze and form into the solid granules. It is possible to receive monodisperse targets from different metals, alloys and salts (diameter of targets is from 30 µm to 1.5 mm). Dispersion by the sizes and speed is less than 1%. The technique allows to receive not only continuous targets, but also hollow targets with dispersion on thickness of wall within 1…2%.